Fibre-reinforced roller compacted concrete transport pavements - Neocleous, Kyriacos; Angelakopoulos, H.; Pilakoutas, Kypros; Guadagnin, Maurizio (My University, 2011)
Concrete pavements are generally more expensive to construct than asphalt pavements, and are thus mostly used in heavily trafficked sections and to reduce maintenance. The research work presented in this paper, however, indicated that the use of rapid construction techniques (such as roller compaction) and materials with lower embodied energy (such as low-energy cements, recycled aggregates and recycled steel fibres) can lead to concrete pavements that are more economical and environmentally friendly than asphalt pavements (40% less energy consumption during the life cycle of the pavement). The first part of this paper presents an overview of this research, which was undertaken as part of the EU FP6 STREP project 'EcoLanes' and investigated the development of long-lasting rigid pavements made with steel-fibre-reinforced roller-compacted concrete. The second part of the paper outlines the work undertaken for the development and optimisation of several trial concrete mixes. It is shown that the flexural behaviour of rollercompacted concrete, under static loads, can be enhanced by the addition of fibres. Furthermore, the results of this study demonstrated the potential of recycling concrete pavements, at the end of their life, for the construction of new pavements.
Keywords: Concrete technology & manufacture; Pavement design; Strength & testing of materials